IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING IN ESTABLISHING BIRRUL WALIDAIN ATTITUDE OF CLASS VIIA STUDENTS AT SMP N 2 KALIWIRO WONOSOBO - Rafidah, Naila; Zuhdi, Ahmad; Lailiyah, Siti (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2024)
This The aims of this study were (1) to find out the learning process of Islamic Religious Education for class VIIA students at SMP N 2 Kaliwiro Wonosobo; (2) Knowing the attitude of birrul walidain class VIIA students at SMP N 2 Kaliwiro Wonosoo; (3) Knowing the implementation of Islamic Religious Education learning in the formation of the attitude of birrul walidain class VIIA students at SMP N 2 Kaliwiro Wonosobo. In this study, qualitative research was used with the object of research namely PAI teachers, and class VIIA students, and student guardians of class VIIA. Collecting data using interview techniques, observation and documentation. The results of the study show that the learning process of Islamic Religious Education in class VIIA SMP N 2 Kaliwiro Wonosobo has a target for students to have noble character, always in the way of Allah SWT, where all of this can be used as a provision to live in society. Even though the students' family backgrounds varied, the attitude of the class VIIA class VIIA students at SMP N 2 Kaliwiro could be said to be quite good. It has been proven that most of the class VIIA students can be devoted to their parents, and do not disobey the orders of their parents. And when the implementation of Islamic Religious Education learning takes place, the average student listens seriously and is already conducive during the learning process.